Structural Changes in the Ibero-American TV Market: Concentration and Convergence against Diversity? - Mastrini, Guillermo; Leiva, María Trinidad García (The Routledge Companion to Global Television, 2019)
This chapter examines the structural changes that can be identified in Ibero-American television in the first 15 years of the 21st century. Taking as a reference the main TV markets in the region (Mexico, Brazil, Argentina and Spain) and their peculiar historical developments, a brief introduction and overview describes their characteristics, potentials and limitations, underlining their strengths, weaknesses and challenges. The analysis, framed in the globalizing phase that cultural products and services are undergoing jointly with their increased digitization, suggests two fundamental drivers of change, summarized in the notions of concentration and convergence. To conclude, policies and recommendations for action are explored, with a view to promote and protect audiovisual diversity.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Argentine (corpus analysé); Argentine (lieu de production du savoir); Brésil (corpus analysé); Espagne (corpus analysé); Espagne (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

More than Copycat Television: Format Adaptation as Performance - Navarro, Vinicius (Global Television Formats: Understanding Television Across Borders, 2012)
As a trend that captured the imagination of Brazilian audiences, the rapid proliferation of dance competitions on network television is meaningful not simply as a domestic phenomenon but also, and particularly, as an illustration of the mechanisms that enable the global popularity of formatted programs. While the shows were locally produced and relied on local talent, they were all based on formats that originated elsewhere, “imported ideas” that were recycled by Brazilian producers. References to foreign versions of the formats were also part of the discourses through which the domestic adaptations were described. As one show followed the other, they invited comparisons not only among themselves but also with their international counterparts. Yet, despite the association with foreign TV shows, the formats were easily incorporated to Brazil’s television culture, a feat that could surprise neither critics nor the industry.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Technologies of Self-Fashioning : Virtual Ethnicities in New Media Art - Jim, Alice Ming Wai (Proceedings of the 21st International Symposium on Electronic Art, 2015)
This paper proposes a theoretical framework with which to dis- cuss the critical engagement of media art projects in Second Life with racialized self-representation, fashion and ethnic dress. Ex- amining Montreal-based Mohawk artist Skawennati’s machinima series, TimeTravellerTM (2008-13), a project of self- determination, survivance and Indigenous futurity, it argues the critically-aware act of ‘virtually self-fashioning’ racialized born- digital identities, or virtual ethnicities, disrupts ways in which today’s vast proliferation of self-technologies enabling the crea- tion, recreation and management of multiple selves, would other- wise remain complicit with neoliberal colour-blind racism
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Orientalismo, poscolonialidad y conocimientos de otro modo: bases, críticas, silencios y continuidades para una discusión político-cultural en el contexto latinoamericano - Estrada, Edwin Jader Suaza (Revista de Estudiantes de Ciencia Política, 2016)
La perspectiva de la modernidad/colonialidad provee un encuadre alternativo para los debates sobre la modernidad, la globalización y el desarrollo desde la periferia latinoamericana del sistema mundo moderno colonial. Las ideas que se exponen en el presente artículo, proporcionan un guía de lectura frente a los principales rasgos del entramado conceptual que rodea a este lugar de enunciación del conocimiento. La perspectiva modernidad/colonialidad aporta una reflexión sobre la cultura y diferentes planos de la realidad social y política, nutrida en debates académicos sustentados no desde una perspectiva intra-epistémica, como los discursos críticos europeos, sino desde la mirada de los receptores de los supuestos beneficios del mundo moderno. Se presenta así un contexto para interpretar Latinoamérica, entendida más como un espacio epistémico y de producción de conocimiento, que como una región objeto de conocimientos pre-establecidos.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Telenovela, an Instrument for Democracy - Eskandari, Sina (Review of European Studies, 2017)
Telenovela shapes important and highly favorite section of the television productions. The T.V. series have moved out from their traditional structure with an entertaining aspect and have been divided into different types and scopes. Taking into consideration the time and the atmosphere of dissemination which the Telenovela programs hold in T.V. antenna, there is a need to conduct studies on sociology of Telenovela more than any other times in the past. This article is an attempt to review the two subject-matters of Telenovela and Narration and their connection with democracy through sociological sporadic studies. This will also present the significance of this genre in T.V. productions at local and international discourses. Observations, field researches and library study methods have been employed in this research.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Colombie (corpus analysé); Espagne (lieu de production du savoir); _Nettoyé

Telenovelas and Transformation: Saving Brazil's Television Industry - Svartman, Rosane (Routledge, Taylor & Francis Group, 2021)
"This book investigates how telenovelas may be the key to the future of Brazilian television and how this content can survive in an interconnected media landscape. Recognised writer and scholar Rosane Svartman considers the particular characteristics of the telenovela format - number of episodes, melodrama influence, and influence of the audience on future writing - to explore how these can be preserved on multimedia platforms, and the challenges this change may present. Svartman further charts the transformations of the telenovela throughout its history and its major influences and unveils the main storytelling elements and writing processes. Chapters examine the business model of Brazilian corporate television within the current context of hypermedia and analyse how this relationship evolves as it is influenced by the new interactive tools and technologies that amplify the audience's power. Merging empirical practices and theory, this book will be of great interest to scholars and students of transmedia storytelling, television studies, and Latin American media, as well as professionals working in these areas"– Provided by publisher.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé